Apple ALMT9 Requires a Conserved C-Terminal Domain for Malate Transport Underlying Fruit Acidity. Issue 2 (26th November 2019) - Li, Chunlong; Dougherty, Laura; Coluccio, Alison E.; Meng, Dong; El-Sharkawy, Islam; Borejsza-Wysocka, Ewa; Liang, Dong; Piñeros, Miguel A.; Xu, Kenong; Cheng, Lailiang
Abstract : An apple malate transporter lacking a conserved C-terminal domain causes low fruit acidity. Abstract: Malate accumulation in the vacuole largely determines apple ( Malus domestica ) fruit acidity, and low fruit acidity is strongly associated with truncation of Ma1, an ortholog of ALUMINUM-ACTIVATED MALATE TRANSPORTER9 ( ALMT9 ) in Arabidopsis ( Arabidopsis thaliana ). A mutation at base 1, 455 in the open reading frame of Ma1 leads to a premature stop codon that truncates the protein by 84 amino acids at its C-terminal end. Here, we report that both the full-length protein, Ma1, and its naturally occurring truncated protein, ma1, localize to the tonoplast; when expressed in Xenopus laevis oocytes and Nicotiana benthamiana cells, Ma1 mediates a malate-dependent inward-rectifying current, whereas the ma1-mediated transmembrane current is much weaker, indicating that ma1 has significantly lower malate transport activity than Ma1. RNA interference suppression of Ma1 expression in 'McIntosh' apple leaves, 'Empire' apple fruit, and 'Orin' apple calli results in a significant decrease in malate level. Genotyping and phenotyping of 186 apple accessions from a diverse genetic background of 17 Malus species combined with the functional analyses described above indicate that Ma1 plays a key role in determining fruit acidity and that the truncation of Ma1 to ma1 is genetically responsible for low fruit acidity in apple. Furthermore, we identified a C-terminal domain conserved in all tonoplast-localized ALMTs essential for Ma1 function; protein truncations into this conserved domain significantly lower Ma1 transport activity. We conclude that the truncation of Ma1 to ma1 reduces its malate transport function by removing a conserved C-terminal domain, leading to low fruit acidity in apple.